Anestesi Umum dengan Intubasi Endotrakeal pada Pasien Atonia Uteri - Aldy Marthin Wajabula; Agus Eko Susilo (Jurnal Anestesi, 2025)
Uterine atony is one of the leading causes of postpartum hemorrhage that can be life-threatening for the patient. Management of uterine atony often involves surgical procedures and the use of general anesthesia to ensure the patient's safety and comfort. This case report presents a patient with uterine atony who underwent surgery with general anesthesia and endotracheal intubation. Endotracheal intubation was chosen to maintain an open airway and prevent aspiration during the procedure. In this case, the selection of appropriate anesthesia and intubation techniques was crucial to managing severe bleeding and maintaining the patient's hemodynamic stability. The success of the procedure highlights the importance of optimal anesthesia preparation and management in patients with critical postpartum conditions.